2013
DOI: 10.1902/jop.2013.120545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tacrolimus and Nifedipine, Alone or in Combination, on Gingival Tissues

Abstract: Results suggest that duration of drug administration is a more important risk factor than drug combination. The results include a potentially new insight about PTEN's role in the etiology of drug-induced gingival overgrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(159 reference statements)
0
4
1
Order By: Relevance
“…Our histomorphometric and stereological results showed that no signs of gingival overgrowth were found in the group administered sirolimus alone, whereas prominent gingival overgrowth was found in groups administered cyclosporine A alone and tacrolimus alone. Many clinical and experimental studies reported that combined drug usage caused much more gingival overgrowth compared with the usage of each drug alone . In contrast to these studies, the results of the present study showed that gingival overgrowth was more prominent in groups administered cyclosporine A and tacrolimus alone compared with combination groups.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our histomorphometric and stereological results showed that no signs of gingival overgrowth were found in the group administered sirolimus alone, whereas prominent gingival overgrowth was found in groups administered cyclosporine A alone and tacrolimus alone. Many clinical and experimental studies reported that combined drug usage caused much more gingival overgrowth compared with the usage of each drug alone . In contrast to these studies, the results of the present study showed that gingival overgrowth was more prominent in groups administered cyclosporine A and tacrolimus alone compared with combination groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Thirty‐six rats were randomly divided into six groups of six rats each, as follows: cyclosporine group: 30 mg/kg body weight of cyclosporine A was administered daily for 8 wk. tacrolimus group: 1.5 mg/kg body weight of tacrolimus was administered daily for 8 wk. sirolimus group: 1.5 mg/kg body weight of sirolimus was administered daily for 8 wk. cyclosporine + sirolimus group: 30 mg/kg body weight of cyclosporine A and 1.5 mg/kg body weight of sirolimus were administered daily for 8 wk. tacrolimus + sirolimus group: 1.5 mg/kg body weight of tacrolimus and 1.5 mg/kg body weight of sirolimus were administered daily for 8 wk. control group: distilled water was administered daily for 8 wk. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10141522] In one of the recent experimental studies using the rat model, authors reported DIGO only after 24 weeks of administration of tacrolimus and Nf, alone or in combination. [23] Differences of drug doses were accounted as the possible reason for such variation in findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has indicated that PTEN also participates in the inflammatory response. Drug‐induced gingival overgrowth is partly driven by decreased PTEN function, which alters the proliferation–apoptosis ratio of fibroblasts (Pamuk et al., 2013). In fibroblast‐like synoviocytes from clinical rheumatoid arthritis specimens and rat models, PTEN expression is downregulated (X.…”
Section: Introductionmentioning
confidence: 99%